Effect of ethanol level in the perception of aroma attributes and the detection of volatile compounds in red wine - Goldner, María Cristina (2009)
Fil: Goldner, María Cristina. Pontificia Universidad Católica Argentina. Facultad de Ciencias Agrarias; Argentina